Why bother death, failure, and fatalistic withdrawal from life. [article]. - Hayes, Joseph
The current research examines the conditions under which death contemplation will reduce, rather than increase, goal-directed activity. By employing a goal-regulation perspective on the problem of death, we hypothesized that death awareness precipitates withdrawal from the goal for continued life when life is experienced as dissatisfying and hope for the future appears bleak. In Study1, participants with low life satisfaction who contemplated goal failure responded to mortality salience with reduced desire for continued life. Studies 2-4 examined general goal motivation. Consistent with the idea that withdrawal from life precipitates a general state of reduced goal motivation, parallel effects were observed on the willingness to delay gratification for future outcomes (Study 2), orientation toward the future (Study 3), and behavioral activation system (BAS) sensitivity (Study 4). Moreover, Study 3 showed that these effects were mediated by a generally pessimistic attitude toward life. finally, Study 5 assessed felt uncertainty and state depression, revealing that withdrawal from life was associated with reduced uncertainty but increased depression. Discussion is focused on implications for theories of threat and defense, and applications for understanding depression and suicide. -- (from the authors)
Keywords: Ward, Cindy L. P; McGregor, Ian; Death; Goal-regulation.; Withdrawal; Suicide; Depression